The Use of Effective Sentences on Procedure Text for Class VII Students of Terpadu Islamic Junior High School, Batujaya - Mahfuzoh, Mala (Lembaga Riset Mutiara Akbar, 2022)
This study aims to analyze the use of effective sentences in procedural texts for seventh grade students of SMP Islam Terpadu Batujaya. This study uses a qualitative approach with a descriptive method which aims to describe objectively the use of effective sentences in students' procedural texts. The research technique used is documentation. The results showed that the students in using effective sentences were quite good. After the writer analyzed the procedural text of students in using effective sentences, the writer concluded that in the procedural text of the seventh-grade students of SMP Islam Terpadu Batujaya it was said to be quite good in the use of effective sentences. However, there are still some students who still do not understand effective sentences and there are still many students who use ambiguous sentences. The author found the use of effective sentences as many as 60 sentences. The characteristics of the effective sentence are 28 sentences (46.67%) of unity, 21 sentences (35%), 2 sentences (3.33%), 8 sentences of variation (13.33%), and parallelism. 1 sentence (1.67%).